Avaliação do desenvolvimento de Mentha crispa L. cultivada em latossolo vermelho contaminado com zinco - Bilmayer, Ana Flávia (2020)
Phytoremediation uses plants to remove soil contaminants, being a low cost alternative that promotes the revitalization of a degraded area. The plant may present specificity as to the type of contaminant to be removed, and studies are necessary to evaluate the tolerance and the extraction rate of the contaminant. For this purpose, this study evaluated the development of the plant Mentha crispa L. cultivated in soil contaminated with increasing concentrations of zinc. Physical and chemical analyzes of the soil were performed, characterizing it as Dystroferric Red Latosol and the maximum soil zinc adsorption capacity of 482.66 mg kg-1 was determined by the Freundlich model, used as a parameter for the arbitrary definition of the soil. Seven zinc concentrations used in the experiment (treatments C1 to C7), plus control treatment (C0) without metal addition. The experimental design was made with 5 replicates of each treatment, totaling 40 samples. The experiment was carried out in a greenhouse under natural conditions of light, humidity and temperature between August and December of 2018, respecting the period of 105 days of growth of the species. During the experimental period, biweekly evaluations were performed regarding the number of shoots, leaves and height of the aerial part of the plant, in addition to monitoring the visual symptoms and daily watering. After the period of exposure to the contaminant, the plant was collected and the parameters such as length and root mass of each of the treatments were also analyzed. Subsequently, the samples were separated into root, stem and leaves and subjected to acid digestion for zinc determination through the flame atomic absorption spectrometer. During the cultivation period, there was a tendency to reduce the number of leaves, shoots and shoot height from the increase of soil zinc concentrations. Toxicity symptoms such as chlorosis, leaf vein purification, leaf size and texture differentiation and epinastia were observed, however, these effects were not detrimental to the species vitality, demonstrating tolerance to high metal concentrations. Plant roots of treatments C5, C6 and C7 had darker color, length and root mass lower than C0, and probably their development was inhibited by the presence of the contaminant. Considering the total amount of zinc absorbed by the plant, the most significant concentrations were found in the leaves, then in the root and stem. Treatments C6 and C7 accumulated a content of approximately 15 and 20 times higher than the control treatment, respectively. For Bioaccumulation and Translocation factors, values greater than one (1) were found, characterizing Mentha crispa L. as a zinc accumulator and phytoextractor plant, translocating it to the aerial parts. Regarding the rate of extraction of the metal from the soil, values between 1.6 and 9.3% were obtained, which makes it possible to use Mentha crispa L. as a phytoremediator in soil contaminated with zinc.